Doppler Shift Extraction from QPSK Mapped OFDM Signal Constellation (Global Journal of Science Frontier Research, 2014)
Doppler effect gives a frequency offset on received OFDM signal in radar system. That offset can be seen as a distortion and rotation of reflected signals QPSK mapping vectors. It is possible to determine moving target velocity by estimating expected value of the distorted signal and then calculating the rotated angle. A mathematical relationship between Doppler frequency shift and rotated angle of QPSK mapping vectors was obtained. The recommended systems will require less computing resources, because Doppler frequency shift calculation could be done during one OFDM symbol.
Keywords: OFDM; radar; constellation; signal processing; QPSK; doppler shift; target